The Implementation of Corporate Social and Environmental Responsibility by Palm Oil Plantation Companies Toward the Community : A Case at PT Daya Labuhan Indah Pangkatan - Lelisari; Putri Habibah Siregar; Nurlaila Nasution (Faculty of Law, Universitas Pekalongan, 2025)
Corporate social and environmental responsibility is a duty for firms involved in operations concerning natural resources, such as palm oil plantations. The palm oil business is a crucial sector in Indonesia; nonetheless, its sustainability frequently poses environmental and social issues. This study seeks to examine the execution of corporate social responsibility (CSR) by PT Daya Labuhan Indah Pangkatan concerning the environment and local communities, along with the challenges encountered in fulfilling these obligations. The study employs a normative juridical methodology, concentrating on the implementation of legal norms and principles derived from positive law, utilising both statutory and conceptual frameworks. To substantiate this, actual study was undertaken within the company. PT Daya Labuhan Indah Pangkatan executes corporate social responsibility initiatives via environmental greening activities in three villages. Contributions comprise 200 mahogany seedlings, 100 glodokan trees, 100 mango saplings, and 200 hybrid coconut trees. In the education sector, PT Daya Labuhan Indah (Wonosari and Sei Deras estates) supplied landfill support to public junior high schools and contributed decorative stones to a local women's organisation. Furthermore, the corporation constructed two public restrooms and a borewell in adjacent settlements. Nonetheless, the application of CSR remains inconsistent and has yet to be institutionalised. It is conducted freely rather than as a formal requirement. The company continues to depend on its parent organisation, PT Wilmar Group, for corporate social responsibility projects. Significant impediments comprise the view of CSR as a fiscal encumbrance, insufficient allocated resources, lack of organised initiatives for community economic advancement, varying interpretations of CSR, and the belief that CSR is not a global imperative.